Day 2 Tue, April 04, 2017 2017
DOI: 10.2118/184550-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Oil Adhesion to Shale Rocks for EOR

Abstract: Significant work is ongoing within the industry to determine a best practice for maximizing oil recovery from fractured oil-wet shale reservoirs. Rapid decline curves are often observed and water flooding can be largely ineffective because of negative capillary pressure. The goal of this work is to identify a chemical solution that can maximize oil and gas recovery in unconventional reservoirs by reduction of hydrocarbon adhesion to shale rocks. In order to evaluate an optimal solution, numerous formulations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In a study related to oil adhesion on Bakken samples, it was shown that an anionic surfactant solution was salt tolerant (30% TDS brine) and thermally stable at 115 °C (Table 6, entry 11). 322 LSW (4% TDS) was better than high salinity brine (22% TDS) in oil recovery via imbibition, and the addition of 1000 ppm of anionic surfactant increased oil recovery for both brines. Similar (but less dramatic) improvements were attained with an amphoteric surfactant.…”
Section: Spontaneous Imbibition Experimentsmentioning
confidence: 94%
See 3 more Smart Citations
“…In a study related to oil adhesion on Bakken samples, it was shown that an anionic surfactant solution was salt tolerant (30% TDS brine) and thermally stable at 115 °C (Table 6, entry 11). 322 LSW (4% TDS) was better than high salinity brine (22% TDS) in oil recovery via imbibition, and the addition of 1000 ppm of anionic surfactant increased oil recovery for both brines. Similar (but less dramatic) improvements were attained with an amphoteric surfactant.…”
Section: Spontaneous Imbibition Experimentsmentioning
confidence: 94%
“…No clear correlation between IFT and oil recovery was observed, and the authors suggest that wettability alteration is the dominant mechanism of recovery. In a study related to oil adhesion on Bakken samples, it was shown that an anionic surfactant solution was salt tolerant (30% TDS brine) and thermally stable at 115 °C (Table , entry 11) . LSW (4% TDS) was better than high salinity brine (22% TDS) in oil recovery via imbibition, and the addition of 1000 ppm of anionic surfactant increased oil recovery for both brines.…”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that anionic surfactant works the best on quartz-rich rock, while on carbonate-rich Wolfcamp, the cationic surfactant performed dominantly . Production improvement by the addition of surfactant was also observed on the Bakken , and Eagle Ford systems.…”
Section: Introductionmentioning
confidence: 86%